Prevalence and Distribution of Carabelli Cusp in Maxillary Molars in Deciduous and Permanent Dentition and Its Relation to Tooth Size in a Group of Iranian Adult and Pediatric Dental Patients - Aminzadeh, Atousa; Jafarzadeh, Samaneh; Aminzadeh, Ania; Ghodousi, Arash (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: Carabelli cusp is a dental morphologic anomaly arising on the palatal side of the mesiopalatal cusp of maxillary first or second molars. It is believed that this cusp is seen in people with larger teeth. Since it has different prevalence among populations, it can be used in forensic dentistry. As well, dentists should be aware of common dental anomalies that might impact dental treatments. In this study, the prevalence of Carabelli cusp and its relation to tooth size in permanent and deciduous dentitions in Iranian population was assessed. Methods: This analytic-descriptive study was performed on 129 (43 deciduous, 86 permanent) patients and their dental casts. First and second molars were observed for the presence of Carabelli cusp. Mesiodistal width of teeth was recorded by using a vernier calliper. The data were analyzed by the Independent t test, Chi-square and Mann Whitney statistical tests using SPSS 18. Results: Frequency of Carabelli trait were respectively 72% and 62% in deciduous and permanent dentitions. No significant difference was seen between males and females in this study in both studied dentitions (P>0.05). Dentitions with Carabelli cusp had larger mesiodistal width compared to other groups in both dentitions (P<0.001). Conclusion: Carabelli cusp in the studied Iranian population was higher compared to other Asian populations. In addition, its bilateral occurrence like a shallow groove in first maxillary molars was related to larger tooth size in both dentitions.